2017
DOI: 10.1111/epi.13981
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of antiepileptic drugs in children and adolescents: A network meta‐analysis

Abstract: This network meta-analysis suggests that the quality of studies should be improved through the use of comparative designs, relevant outcomes, appropriate follow-up length, and more reliable inclusion criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 68 publications
(111 reference statements)
0
30
1
6
Order By: Relevance
“…Finally, even in areas where RCTs exist, there are still important deficiencies in the quality of the information available. As eloquently stated in a recent metanalysis of pediatric RCTs in epilepsy, “the quality of studies should be improved through the use of comparative designs, relevant outcomes, appropriate follow‐up length, and more reliable inclusion criteria.”…”
Section: From Clinical Trials To Clinical Practicementioning
confidence: 99%
“…Finally, even in areas where RCTs exist, there are still important deficiencies in the quality of the information available. As eloquently stated in a recent metanalysis of pediatric RCTs in epilepsy, “the quality of studies should be improved through the use of comparative designs, relevant outcomes, appropriate follow‐up length, and more reliable inclusion criteria.”…”
Section: From Clinical Trials To Clinical Practicementioning
confidence: 99%
“…Approximately 1% of the general population suffers from epilepsy, which is a chronic disorder characterized by spontaneous recurrent seizures and an increased risk of comorbid conditions, particularly cognitive impairment, anxiety, depression, and sudden unexpected death (Hauser et al, ; Tellez‐Zenteno, Patten, Jette, Williams, & Wiebe, ). Up to 40% of all patients with epilepsy continue to experience seizures and comorbid features despite optimal pharmacological treatment, and many antiepileptic drugs have significant side effects that limit their use (Berg, ; Hu et al, ; Reynolds, ; Rosati et al, ). More effective and specific antiepileptic interventions are therefore urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis, LTG was superior in terms of tolerability, but carbamazepine monotherapy showed a superior trend for seizure control [7]. However, other metaanalyses have reported that the best option for seizure outcome and tolerability was LTG in focal epilepsy [1,8]. LTG showed better tolerability than carbamazepine in two randomized controlled studies, although the studies were limited by the small sample size of pediatric patients [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited because it was an observational study and therefore had less impact than a randomized controlled study. A randomized controlled study that directly compares the effects of LTG and OXC is needed, although studies have evaluated comparable antiepileptic drugs in pediatric focal epilepsy patients by meta-analysis [8].…”
Section: Discussionmentioning
confidence: 99%